Frameworks for modelling the potential longer-term costs and consequences of self-monitoring of blood pressure (SMBP) during pregnancy - Campbell, H; Chappell, L; McManus, R; Tucker, K; Rivero Arias, O (Oxford Population Health, 2024)
Aims: To develop model frameworks to be able to explore the potential long-term costs and effects of future interventions that may combine self-monitoring of blood pressure (SMBP) with targeted blood pressure (BP) management policies for the prevention of hypertension-related complications during pregnancy. Methods: Two model frameworks were constructed; the first focussed upon women at risk of developing pregnancy hypertension, and the second upon women with existing pregnancy hypertension. The model structures were developed using expert clinical opinion and the published literature. Modelled pregnancy pathways included the complications of pregnancy hypertension (for example pre-eclampsia and stroke). The longer-term risks of developing chronic hypertension and cardiovascular disease following pregnancy hypertension and pre-eclampsia were simulated using a Markov model over a 10-year period. Health care costs were modelled and health outcomes were expressed as quality-adjusted life years (QALYs). Event probabilities, costs and utility scores were informed by two randomised trials conducted during the same programme of work and the published literature, and were entered as distributions to enable probabilistic sensitivity analysis. The model was run for a range of different hypothesised intervention effect sizes and implemented so as to be able to simulate results for different cohorts of women with varying risk factors. Results: We present no definitive cost-effectiveness results, instead running a series of hypothetical scenarios to illustrate the capabilities of the models. For example, simulating a hypothetical scenario in which a new SMBP-guided intervention could reduce the risk of a pregnant women developing pre-eclampsia by 10%, the modelling suggested that long-term cost-effectiveness could potentially vary between hypertensive pregnant women and women at risk of pregnancy hypertension. This is because hypertensive women face a greater likelihood of developing associated complications both during and following pregnancy, in turn suggesting a greater absolute level of benefit from a 10% reduction in complications via the mechanism of better BP control. Such hypotheses would of course require empirical testing in practice. The model frameworks developed permit the exploration of cost-effectiveness results for cohorts of women with different risk factors and potential interventions of varying levels of effectiveness, and can be adapted and further developed by researchers for use within their own settings. Conclusions: Model frameworks have been developed that can be used to begin to explore the potential long-term cost-effectiveness of adding novel targeted blood pressure management policies to SMBP during pregnancy.